2020
DOI: 10.1021/acs.jpcc.9b10479
|View full text |Cite
|
Sign up to set email alerts
|

From Collisions to Bundles: An Adaptive Coarse-Grained Model for the Aggregation of High-Aspect-Ratio Carbon Nanotubes

Abstract: We present an adaptive mesoscale model for carbon nanotube (CNT) systems. In our model, CNTs are represented as a chain of nodes connected by tensile and torsion springs to describe stretching and bending of the chain with intermolecular interactions being calculated using a mesoscopic Lennard-Jones potential. Computational adaptivity was achieved by dynamically adjusting node spacing and number during the simulation to optimise the number of simulated particles and lower computational effort. Adaptive simulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 43 publications
1
11
0
Order By: Relevance
“…It was demonstrated that the time scale for CNT collision and bundle formation is 0.3-42 s. Recently, they proposed an adaptive mesoscale model for CNTs in a FCCVD system. [155] This model provides a tool to study the bundling dynamics and to show the aggregation state of CNTs. Also, they systematically investigated the formation process of nanoparticles and the supply of carbon source during continuous synthesis of CNT aerogel.…”
Section: Ropes and Fibersmentioning
confidence: 99%
“…It was demonstrated that the time scale for CNT collision and bundle formation is 0.3-42 s. Recently, they proposed an adaptive mesoscale model for CNTs in a FCCVD system. [155] This model provides a tool to study the bundling dynamics and to show the aggregation state of CNTs. Also, they systematically investigated the formation process of nanoparticles and the supply of carbon source during continuous synthesis of CNT aerogel.…”
Section: Ropes and Fibersmentioning
confidence: 99%
“…Although mDEM has the necessary accuracy, developing faithful computational models for the CNT films described in Section 3 is still challenging. In addition to the difficulties associated with identifying the three-dimensionality of the film structure from the SEM and TEM images, we recognize that the multiscale structure observed by electron microscopy is the result of the vdW-driven CNT coagulation during synthesis, which involves direct CNT-CNT collisions in the gas phase, 21 and during and after the collection onto the filter substrate. While the former involves zipping of individual CNTs, the later stage is likely dominated by the bundle-bundle interaction processes.…”
Section: Mdem Simulations Of Spontaneous Densification Of "Pristine" ...mentioning
confidence: 99%
“…Currently, the dynamical simulations of CNT films rely on numerical approaches, which are still under development and validation. In this respect, a recent theme in the development of numerical models is based on the idea of coarse-graining, [19][20][21][22] where the goal is to develop computationally tractable models of reduced complexity, while preserving a set of target properties to a sufficient accuracy. One of the first developed models was based on the simple bead-and-spring (B&S) polymeric chain model, 19 which is usually trained to reproduce elastic and adhesion properties of CNTs.…”
Section: Introductionmentioning
confidence: 99%
“…The CNT median diameters were analyzed to be 16.4, 18.9, and 25.4 nm for field intensities of 0.23, 0.35, and 0.75 kV cm –1 , respectively. Our recent study on collision rates between CNTs 54 and the alignment of CNTs into bundles 55 has shown few parameters with which to vary the number of CNTs per bundle and, thus, alter the fundamental aerogel structure. We hypothesize, on the basis of our previous work, that the characteristic collision time for aligned tubes increases (i.e., longer time between collisions) as the collision cross-section of two parallel linear structures is smaller.…”
Section: Results and Discussionmentioning
confidence: 99%